Pengaruh Keaktifan Organisasi Kemahasiswaan dan Civic Skills terhadap Kesiapan Mahasiswa Menyusun Tugas Akhir di FKIP UNTIRTA - Maryani Maryani; Ratna Sari Dewi; Reza Mauldy Raharja (YASIN, 2026)
Students’ readiness to complete their final project is determined not only by academic ability but is also influenced by organizational experience and citizenship skills. This study aimed to examine the effect of students’ active participation in student organizations and civic skills on their readiness to complete their final project. A quantitative approach with a correlational design was employed involving FKIP Untirta students who were active in Hima PPKn, DPM, and UKM Belistra in the 2025 period, using stratified random sampling. The results of the analysis showed a significant effect of student organizational involvement and civic skills on students’ readiness to complete their final project, as indicated by significance values of 0.010 < 0.05 for organizational involvement and 0.000 < 0.05 for civic skills, as well as t-values for X₁ of 2.627 > t-table 1.65787 and for X₂ of 5.927 > t-table 1.65787. The coefficient of determination (adjusted R²) of 0.537 indicates that the two independent variables explain 53.7% of the variance in students’ readiness to complete their final project, while the standardized coefficients beta show that civic skills (0.543) have a stronger effect than student organizational involvement (0.241). These findings conclude that active participation in student organizations and civic skills have a positive influence on students’ readiness to complete their final project at FKIP Untirta and highlight the importance of strengthening organizational experiences and citizenship skills within student development programs and final project supervision.